Immune Complex Membranoproliferative Glomerulonephritis Associated with Transjugular Intrahepatic Portosystemic Shunts in Alcoholic Cirrhosis: Two Case Reports - Hernández-Jaras, Julio (Med Princ Pract, 2017)
OBJECTIVE: To report on 2 patients with alcoholic cirrhosis who were treated with transjugular intrahepatic portosystemic shunt (TIPS) placement. CLINICAL PRESENTATION AND INTERVENTION: The 2 patients had a history of alcoholic cirrhosis, and TIPS surgery was performed on them. In both cases, 4 months after TIPS placement, proteinuria was observed along with histological alterations characteristic of immune complex membranoproliferative glomerulonephritis (MPGN). CONCLUSION: The TIPS in one patient was successful without immediate complications, while the other patient was referred for a combined liver-kidney transplant. In both cases, immune complex MPGN might have developed after TIPS placement probably due to a reduced immune complex clearance.